Oropharyngeal Muscle Exercise Therapy Improves Signs and Symptoms of Post-stroke Moderate Obstructive Sleep Apnea Syndrome - Ye, Dongmei; Chen, Chen; Song, Dongdong; Shen, Mei; Liu, Hongwei; Zhang, Surui; Zhang, Hong; Li, Jingya; Yu, Wenfei; Wang, Qiwen (Frontiers in Neurology, 2018)
The primary aim of the current study was to assess the effects of oropharingeal muscle exercises in obstruction severity stroke patients with OSAS. The secondary aims were to evaluate the effects of the exercises on rehabilitation of neurological function, sleeping and morphology change of upper airway. An open-label, single-blind, parallel-group, randomized, controlled trial was designed. Fifty post-stroke patients with moderate OSAS were randomly assigned into 2 groups (25 in each group). For the therapy group, oropharyngeal muscle exercise was performed during the daytime for 20 min, twice a day, for 6 weeks. The control group was subjected to sham therapy of deep breathing. Primary outcomes were the obstruction severity by polysomnography. Secondary outcomes included recovery of motor and neurocognitive function, personal activities of daily living assessment (ADL)), sleep quality and sleepiness scale. It also included upper airway magnetic resonance imaging (MRI) measurements. Assessments were made at baseline and after 6-week exercise. Finally, 49 patients completed the study. The apnea–hypopnea index, snore index, arousal index, and minimum oxygen saturation improved after exercise (P < 0.05). Oropharyngeal muscle exercises improved subjective measurements of sleep quality (P = 0.017), daily sleepiness (P = 0.005), and performance (both P < 0.05) except for neurocognition (P = 0.741). The changes in obstruction improvement, sleep characteristics and performance scale were also associated with training time, as detected by Pearson’s correlation analysis. The anatomic structural remodeling of the pharyngeal airway was measured using MRI, including the lager retropalatal distance (P = 0.018) and shorter length of soft palate (P = 0.044) compared with the baseline. Hence, oropharyngeal muscle exercise is a promising alternative treatment strategy for stroke patients with moderate OSAS.